Analisis Manajemen Risiko pada Bisnis Tanaman Hias di Kecamatan Kramat, Kabupaten Tegal - Sari, Fera Adelia; Amirah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to analyze the level of risk and risk management strategies in ornamental plant kiosk businesses in Kramat Subdistrict, Tegal Regency. The research method used a descriptive quantitative approach with data collection through a questionnaire covering four main risk aspects—namely production, market, financial, and operational risks—as well as one aspect of risk mitigation strategy, which was assessed using a 1-5 Likert scale. The results show that 45% of risk aspects are in the very high category, 35% in the high category, 15% in the moderate category, and 5% in the low category. The most dominant risks come from production and market factors, such as extreme weather changes, pest attacks, and seasonal demand fluctuations. However, business actors have implemented quite effective risk mitigation strategies, such as crop diversification, routine evaluation, and cooperation with suppliers. This study emphasizes the importance of strengthening managerial capacity, access to capital, and optimizing digital marketing to improve the resilience of ornamental plant businesses in the region